Coral rubble facilitates feeding opportunities for invertivorous reef fishes on tropical coral reefs - Lisa S. Goberdhan; Gareth J. Williams; Shaun K. Wilson; Rodney Melanie; Nicholas A. J. Graham (Coral Reefs, 2026)
Invertivorous reef fishes play a crucial role in coral reef ecosystems, transferring energy from benthic invertebrates to higher trophic levels. They rely on a diverse array of benthic habitats to forage for invertebrate prey. However, climate change and local stressors are reshaping reef habitats, with coral rubble becoming increasingly dominant. Despite low structural complexity, coral rubble supports abundant invertebrates, presenting both opportunities and challenges for invertivorous fish. However, the foraging ecology of fish in rubble habitats remains understudied, limiting our ability to predict their responses to ongoing reef degradation. By combining 28 yrs of reef fish and benthic community monitoring data with targeted rubble disturbance and fish foraging experiments on reefs in the inner Seychelles Islands, we test whether invertivorous reef fish community structure on coral rubble habitats is influenced by reefs characterised by distinct benthic regimes (rubble-dominated, hard substrate-dominated or macroalgal dominated) and by opportunistic feeding mechanisms. We show that invertivorous reef fish communities are highly distinct among benthic regimes at the reef scale, and benthic regime influences the invertivorous reef fish community associated with static, unconsolidated rubble habitats. However, when unconsolidated rubble habitats are physically disturbed, differences among benthic regimes diminish, and a consistent subset of invertivorous fishes rapidly exploit rubble habitats across regimes. These findings are important in shaping our understanding of how reef fish communities may interact with future reef environments, and the species that may have a competitive advantage on rubble-dominated reefs, influencing trophic interactions and resource use.